Supernumerary Tooth in Ectopic Position in the Mandible: Case Report - Arruda, Daiana Arruda do; Sá, Larisse Eduarda Nunes; Silva, Maria Sarony Araújo; Mororó, Jaqueline Pernambuco; Martorell, Karla Isabel Girón; Sampaio, Eduardo Ribeiro; França, Samuel Rocha; Ferreira Filho, Josfran da Silva (Brazilian Journal of Case Reports, 2025)
Ectopic and impacted teeth represent distinct conditions that, when combined, can lead to significant complications, such as damage to adjacent structures. Supernumerary teeth can also cause functional and aesthetic alterations, primarily related to the eruption of permanent teeth. The diagnosis of these conditions requires a clinical and radiographic examination, as well as surgical planning. This article aims to report a clinical case of the surgical removal of an impacted supernumerary tooth, located in an inverted intraosseous position in the mandibular body near the basal cortical bone. A 15-year-old female patient was referred to the Oral and Maxillofacial Surgery and Traumatology service. Computed tomography revealed that the tooth was in continuity with the mandibular base and in close contact with the mental nerve. Surgery is often the treatment of choice to prevent complications such as mandibular fractures and cystic lesions. Each case should be planned individually, and the dental surgeon must be aware of the treatment options and complementary exams to ensure a safe and effective outcome for the patient.